Obtencao e interpretacao de dados de Reflexao Sismica Superficial (Rasa) - exemplos e aplicacoes - Jose, C. (My University, 1990)
Successful application of shallow seismic reflection method is related directly to the ability of the ground to transmit high-frequency seismic energy from a seismic source. The dominant frequencies of reflection data are in the range of 50 to 100 Hz and depend on the surface materials and water table. A spread of geophones send the siemsic signal to be recorded on a 12, 24 or 48 channel portable seismograph, using a single high-frequency geophone per channel. Although it is possible to find seismographs with display and processing unities, it is also possible to transfer digitalized data to a personal computer to be processed and interpreted by using specific programs. Some results of two recent field studies to specify the underground structure in the tidal flats area of Baie St. Paul (Quebec-Canada) and in glacial terrains, in the Waterloo (Ontario-Canada) region. -from English summary
The geophysical shallow seismic reflection applied to groundwater analysis: case studies
Keywords: aquifer characteristics; glacial terrain; groundwater exploration; seismic reflection; tidal flat; water table height; Canada, Ontario, Waterloo; Canada, Quebec, Baie St. Paul